2018
DOI: 10.1016/j.cell.2018.02.047
|View full text |Cite
|
Sign up to set email alerts
|

Common PIEZO1 Allele in African Populations Causes RBC Dehydration and Attenuates Plasmodium Infection

Abstract: Hereditary xerocytosis is thought to be a rare genetic condition characterized by red blood cell (RBC) dehydration with mild hemolysis. RBC dehydration is linked to reduced Plasmodium infection in vitro; however, the role of RBC dehydration in protection against malaria in vivo is unknown. Most cases of hereditary xerocytosis are associated with gain-of-function mutations in PIEZO1, a mechanically activated ion channel. We engineered a mouse model of hereditary xerocytosis and show that Plasmodium infection fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
270
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(287 citation statements)
references
References 73 publications
15
270
1
1
Order By: Relevance
“…Much like the Piezo family of MSC, which was found to be involved in touch (Ranade et al, 2014b), proprioception (Woo et al, 2015), lung inflation (Nonomura et al, 2017), vascular development (Ranade et al, 2014a), and red blood cell volume regulation (Cahalan et al, 2015;Ma et al, 2018), TACAN is expressed in many tissues and likely to play important roles in several mechanotransduction processes. TACAN also has a homolog in mammalian cells, TMEM120B, but its heterologous expression did not increase mechanically-evoked currents ( Figure S6).…”
Section: Discussionmentioning
confidence: 99%
“…Much like the Piezo family of MSC, which was found to be involved in touch (Ranade et al, 2014b), proprioception (Woo et al, 2015), lung inflation (Nonomura et al, 2017), vascular development (Ranade et al, 2014a), and red blood cell volume regulation (Cahalan et al, 2015;Ma et al, 2018), TACAN is expressed in many tissues and likely to play important roles in several mechanotransduction processes. TACAN also has a homolog in mammalian cells, TMEM120B, but its heterologous expression did not increase mechanically-evoked currents ( Figure S6).…”
Section: Discussionmentioning
confidence: 99%
“…Using a comparative genomics approach, a common PIEZO1 polymorphism was 49 identified in healthy individuals of African descent that may be under positive selection and act as 50 a gain-of-function allele (MA et al 2018). The mutation, E756del (rs572934641), is a 3 nucleotide 51 deletion in a coding region of the gene that includes ~60 bp of short tandem repeats.…”
Section: Introduction 19mentioning
confidence: 99%
“…E756del was classified as a gain-of-function mutant based on studies in HEK cells, where it 53 displayed a prolonged inactivation time constant after mechanical stimulation as compared to 54 wild-type PIEZO1. Results from in vitro assays using the human malaria parasite P. falciparum 55 suggested that parasite growth was impaired in RBCs from E756del heterozygotes as compared 56 to wild-type RBCs (MA et al 2018). Together, these findings raise the intriguing possibility that 57 the PIEZO1 E756del allele may be protective against severe malaria in humans.…”
Section: Introduction 19mentioning
confidence: 99%
See 1 more Smart Citation
“…Small amounts of cfDNA are detectable in plasma of healthy individuals, while increased levels are observed in pathologic conditions, including cancer, trauma, stroke, chronic inflammation and infection, myocardial ischemia, and autoimmune diseases, proportionally to clinical severity. 1 Hematopoietic cells are likely to contribute to a certain amount of measurable cfDNA, being in close contact with the plasma moiety.…”
Section: Supporting Informationmentioning
confidence: 99%